Blood neuroexosomal excitatory amino acid transporter-2 is associated with cognitive decline in Parkinson’s disease with RBD - Leng, Bing; Sun, Hairong; Li, Mengfan; Zhao, Junwu; Liu, Xiaoxiao; Yao, Ran; Shen, Tengqun; Li, Zhenguang; Zhang, Jinbiao (Frontiers in Aging Neuroscience, 2022)
Background Rapid eye movement (REM) sleep behavior disorder (RBD) predicts cognitive decline in Parkinson’s disease (PD) patients without dementia. However, underlying mechanisms remain unknown. Accumulating studies suggest glutamatergic system dysregulation is associated. Objective To examine the effect of RBD on the rate of cognitive decline in PD patients and investigate whether plasma levels of the neuroexosomal vesicular glutamate transporter-1 (VGLUT-1) and excitatory amino acid transporter-2 (EAAT-2) are altered in PD patients with RBD. Methods This study included 157 newly diagnosed cognitive normal PD patients and 70 healthy controls (HCs). Based on one-night polysomnography recordings, the PD subjects were divided into PD with and without RBD (PD-RBD and PD-nRBD) groups. All participants received a complete clinical and neuropsychological evaluation at baseline. Plasma levels of neuroexosomal VGLUT-1 and EAAT-2 were measured by ELISA kits. After a 3-year follow-up, we evaluated baseline plasma levels of neuroexosomal glutamate transporters in each group as a predictor of cognitive decline using MoCA score changes over 3 years in regression models. Results Plasma levels of neuron-derived exosomal EAAT-2 and VGLUT-1 were significantly lower in PD patients than in HCs. Plasma levels of neuroexosomal EAAT-2 were significantly lower in PD-RBD than PD-nRBD group at baseline. At the 3-year follow-up, PD-RBD patients presented greater cognitive decline. Lower baseline blood neuroexosomal EAAT-2 predicted cognitive decline over 3 years in PD-RBD patients (β = 0.064, P = 0.003). Conclusion These findings indicate that blood neuroexosomal EAAT-2 is associated with cognitive decline in PD with RBD.